A methodological framework for attributing the burden of animal disease to specific causes - Bruce, M.; Jemberu, Wudu T.; Larkins, A.J. (World Organisation for Animal Health, 2024)
The Global Burden of Animal Diseases provides an analytical framework to measure the overall health of various farmed animal populations, to estimate the farm-level burden of different diseases, incorporating production losses due to morbidity and mortality as well as health expenditure, and to identify the wider economic and human health impacts of animal disease. Attributing the burden of animal diseases to specific causes or groups of causes requires methodological choices, including the classification of diseases and the resulting health states that manifest in loss of production. The aim of this article is to address the key challenges in the process of estimating farm-level disease burden, including ambiguity in terminology, data availability and collation, and adjustments for comorbidity. Using infection with zoonotic Brucella spp. in small ruminants as an aetiological cause of disease and abortion as a sequela of multiple diseases, practical examples of the framework are provided. Cause-specific attribution of the burden of animal disease captures temporal and spatial trends, an understanding of which is essential for planning, monitoring and evaluating animal health programmes and disease interventions.